A simple assay for measuring tannin‐protein precipitation capacity offers insights into the diet and food choice of black howler monkeys (Alouatta pigra) - Aristizabal Borja, John Fredy; Alvarez‐Velazquez, María Fernanda; Espinosa‐Gómez, Fabiola Carolina; Garber, Paul A.; Serio‐Silva, Juan Carlos (2024)
Phenolics, like tannins, are plant‐specialized metabolites that play a protective role against herbivory. Tannins can reduce palatability and bind with proteins to reduce digestibility, acting as deterrents to feeding and impacting nutrient extraction by herbivores. Some assays measure tannin and total phenolics content in plants but lack determination of their biological effects, hindering the interpretation of tannin function in herbivory and its impacts on animal behavior and ecology. In this study, we successfully applied the radial diffusion assay to assess tannin protein precipitation (PP) capacity and evaluate the anti‐nutritional effects of tannins in food plants (n = 24) consumed by free‐ranging black howler monkeys (Alouatta pigra) in Tabasco, Mexico. We found PP rings in five plant species consumed by the monkeys. The mature fruit of Inga edulis was the most consumed food plant, despite having a high tannin PP capacity (56.66 mg tannic acid equivalent/g dry matter). These findings highlight the presence of tannins in the black howler diet and provide insight into the primates' resilience and potential strategies for coping with antinutritional aspects of the diet.